Design of Ripple Free Single Phase Isolated Converter using DC Active Filter with Centre Tap Transformer - Balamurugan, A. Sandhiya, A. Peer Fathima, P. (Journal of Experimental Sciences, 2011)
A ripple current reduction method is proposed that does not require additional switching devices. A current ripple that has twice the supply frequency of the power supply is generated in the dc part when a single-phase pulse width modulated inverter is used for a grid connection. The current ripple causes shortening of the lifetime of electrolytic capacitors, batteries, and fuel cells. The proposed circuit realizes a dc active filter function without increasing the number of switching devices, because the energy buffer capacitor is connected to the center tap of the isolation transformer. In addition, the buffer capacitor voltage is controlled by the common-mode voltage of the inverter. The features of the proposed circuit are described and Simulation results are presented.Simulation results proves the ripple reduction, to approximately 20% that of the conventional circuit.